Pulmonary co-infection with Cryptococcus neoformans and Mycobacterium tuberculosis in a middle-aged male, case report and literature review. Issue 2 (6th April 2023) - Chen, Hanlu; Qiu, Chunning; Cen, Ke; Wu, Shenghai
Abstract : Co-infection with Cryptococcus neoformans and Mycobacterium tuberculosis is rare, especially in people with normal immune function. We present a case of a middle-aged man with tuberculosis complicated with cryptococcal pneumonia. He was admitted for chest distress, productive cough with white sputum and fever. The diagnosis was based on the positive detection of Mycobacterium tuberculosis RNA in bronchoalveolar lavage fluid (BALF), positive T-SPOT by ESAT-6 and finding Cryptococcus neoformans in BALF culture.